Sustainable Development of the Energy Sector in the Context of Socioeconomic Cohesion in France, Germany, and Poland - Magdalena Kowalska; Agata Gniadkowska-Szymańska; Anna Misztal; Michał Comporek (Energies)
The energy sector is crucial for the country’s stable and lasting socioeconomic development and for implementing environmentally friendly technologies. The sustainable development of the energy sector takes place in three pillars: economic, social, and environmental. It means improving economic results while increasing the share of alternative energy sources. The paper aims to assess the impact of socioeconomic cohesion on the sustainable development of the energy sector in France, Germany, and Poland. We created indicators of sustainable development and socioeconomic cohesion. We used correlation analysis to examine the relationships. Additionally, we created a single- and multi-equation model, which we reset using the ordinary least squares method and Seemingly Unrealized Regression. The results of the linear correlation coefficients show a very strong relationship between socio-economic cohesion and the sustainable development of the energy sector in Poland (Pearson’s R 0.94), a weaker correlation in Germany (0.811), and the weakest in France (0.59). The results suggest that the relationship is strongest in the country with the lowest economic development and the smallest share of renewable energy, a significant positive impact on the sustainable development of the energy sector. The strength of this impact is varied in the countries studied, indicating a different level of advancement and development in the countries studied.